STRATEGI PENGEMBANGAN POTENSI PARIWISATA PANTAI JEMPLUNG SEBAGAI DESTINASI WISATA UNGGULAN DI KABUPATEN SUMBAWA - Rahma, R; Haryadi, Wahyu (Pusat Riset dan Publikasi, 2024)
This study aims to analyze the development strategy for the tourism potential of Jemplung Beach as a leading tourist destination in Sumbawa District. The type of this study was descriptive with a qualitative approach. The type of data used in this study was qualitative data obtained directly from primary sources. The determination of informants in this study was carried out using purposive sampling techniques with the consideration that they know and have various basic information needed in this study. Based on these considerations, the informants in this study numbered 15 people consisting of Village Heads, Tourism Attraction Managers, Local Residents, and Visitors. The collected data was analyzed descriptively using the SWOT analysis model to formulate alternative development strategies based on internal and external conditions at the Jemplung Beach tourist attraction in Sumbawa District. Based on the results of the SWOT analysis, four alternative strategies were obtained in developing the tourism potential of Jemplung Beach as a leading tourist destination in Sumbawa District, namely the S-O strategy, S-T strategy, W-O strategy, and W-T strategy. S-O strategy, S-T strategy, W-O strategy, and W-T strategy. In general, in formulating tourism object development planning, it should be done by considering the potential and capacity of the local community. This aims to increase local community participation. Thus, local communities can become the main actors in various tourism activities so that they can directly feel the benefits of the existence of tourism objects in the form of increasing income and welfare.